DYSARTHRIA SPEECH DISORDER ANALYSIS AS SEEN IN THE THEORY OF EVERYTHING FILM BY JAMES MARSH - Irwansyah - (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
Dysarthria is a type of motor speech disorder such as slurred speech and sometimes difficult to understand due to problem in articulation. ALS influence speech ability through every nerve that was controlling to the complex of speech organ problems. The researcher used three theories to analyze the data, dysarthria from Joseph R. Duffy (2013), articulation from George Yule (2010), and speech impairments from William Lee Heward (1996). The researcher used qualitative research by Ranjit Kumar (2011). Meanwhile, in data collection techniques, the researcher used documentation techniques by Sudaryono (2006). In the process of analyzing data, the researcher used descriptive analysis method from Creswell (2009). The researcher aim to represent valid data based on the findings that has analyzed. The results in dysarthria research, the researcher had found out thirteen data from five kinds of dysarthria experienced in main character is Stephen as a sufferer of ALS, they were; two flaccid, three spastic, two ataxicg, four hyperkinetic, and two mixed. The dominant problem of dysarthria is hyperkinetic that affected by speech organ functions of ALS disease. The researcher had found seven data to identify the articulation influence to speech impairments associated with dysarthria, they were; five speech sound disorders influenced by failures in the articulation that affect in loss/weakness of sound with difficulty to speech movements, and slurred speech. Two fluency disorders that influenced by abnormalities in speech motoric like as uncontrolled/broken and excessive tension in speech